Szólád, Ungarn: Auswertungsarbeiten am langobardenzeitlichen Gräberfeld: Katalogarbeiten, Genetik, Publikation und interdisziplinäre Arbeitstreffen - Winger, Daniel; von Freeden, Uta; Vida, Tivadar (e-Forschungsberichte des DAI, 2023)
The Langobard cemetery of Szólád at Lake Balaton was unearthed in 2003 when opening up a motorway feeder from Szólád to the M7 motorway. After the initial find of a male burial the whole area was surveyed with geophysics uncovering further burials. Between 2005 and 2007 and in 2010 in different areas of the Szólad ridge research excavations were executed, focussing the Langobard cemetery, but also documenting Neolithic, Iron Age, Late Antiquity and Pannonian Avar structures. From the beginning the excavation design was interdisciplinary and oriented towards bio-archaeological analysis – that was still carried out in 2015.